Kualitas Layanan Sebagai Strategi Peningkatan Kepuasan Penumpang Melalui Inovasi Layanan di Bandara Tjilik Riwut - Christina Rosalia; Lelo Sintani; Yunikewaty Yunikewaty (FKIP, Universitas Palangka Raya, 2023)
The COVID-19 pandemic has affected many sectors around the world, one of which is the air transportation sector. Based on this it becomes very important for airports to quickly adapt to adjust their services according to changing conditions. This study aims to measure and analyze the effect of service quality and service innovation on passenger satisfaction during the COVID-19 pandemic at Tjilik Riwut Airport, Palangka Raya.This study uses quantitative research methods and to obtain data using questionnaires to respondents. The sample of this study consisted of 170 respondents, namely passengers and the public who had used the services as passengers at Tjilik Riwut Airport, Palangka Raya. The sampling technique in this research is using non-probability sampling through purposive sampling method. Data analysis in this study used the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach.The results showed that (1) the effect of service quality on passenger satisfaction with a value of 0.601 and a P-value of 0.000 was significantly positive. (2) The effect of service quality on service innovation with a value of 0.665 and a P-value of 0.000 is positive and significant. (3) The effect of service innovation on passenger satisfaction with a value of 0.361 and a P-value of 0.000 is positive and significant. (4) The role of service innovation in mediating the effect of service quality on passenger satisfaction with a path coefficient value of 0.240 and a P-value of 0.000 is significantly positive.